Characterization and Prediction of the Non-Bonded Molecular Interactions between Racemic Ibuprofen and α-Lactose Monohydrate Crystals Produced from Melt Granulation and Slow Evaporation Crystallization - Zulfahmi Lukman; Nornizar Anuar; Noor Fitrah Abu Bakar; Norazah Abdul Rahman (Indonesian Journal of Chemistry, 2020)
Granulation of racemic ibuprofen (±IBP) and α-lactose monohydrate (ALM) at a slightly lower (±IBP) melting point is an efficient method of binding the active pharmaceutical ingredients (API) and excipient in a binderless condition. However, the co-crystals may be formed from recrystallization of ±IBP on ALM. The objective of this study is to evaluate the tendency of co-crystal formation of granules (3:7 w/w ratio of ±IBP:ALM) by melt granulation process. Second, investigate the recovery of crystals from polyethylene glycol (PEG) 300 solutions containing ±IBP-ALM mixtures. Characterizations of the samples were performed using Fourier Transform Infrared (FTIR) spectroscopy, Differential Scanning Calorimetry (DSC) and Powder X-Ray Diffraction (PXRD) system of the ±IBP-ALM granules produced from melt crystallization and harvested crystals from PEG 300 solution which is produced using slow evaporation crystallization. Crystal analysis of solution containing ±IBP-ALM mixtures revealed that the crystals formed were not co-crystals. Molecular interactions assessment through binding prediction between ±IBP and ALM terminating surfaces was conducted using molecular modelling technique. The result showed that the favorable binding sites of ±IBP molecules were on the surfaces of (0-20), (1-10), (001) and (011) ALM crystals. Successful binding prediction by the attachment energy method has proven that the co-crystal formation between these molecules is theoretically possible.